On the asymptotics of the maximal eigenvalue for a family of branching processes - Yeleyko, Ya. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish an asymptotic representation of the maximal eigenvalue ρε for a family of branching processes with arbitrary number of types of particles which are close to critical ones.